Analisis Sistem Informasi Manajemen Presensi Loyalitas Pegawai Asn Melalui Aplikasi Pusaka Di Kantor Kementerian Agama, Kanwil Kemenag Sulawesi Barat/ Mamuju - Rahmana, Resky; Khatimah B, Husnul; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of information technology has encouraged government institutions to optimize digital systems in human resource management, including aspects of attendance management for civil servants (ASN). The Ministry of Religious Affairs of the Republic of Indonesia has implemented an application-based attendance system through the PUSAKA Super App as part of the digital transformation of personnel services. This study aims to analyze the management information system of ASN attendance through the PUSAKA application and its influence on employee loyalty at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province, particularly in Mamuju.This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation studies. The results indicate that the implementation of the PUSAKA application has improved  discipline and transparency in ASN attendance, which has a positive impact on employee loyalty. The digital attendance system provides convenience, data accuracy, and fairness in attendance assessment. However, the implementation still faces technical challenges, such as limited internet connectivity and application disruptions. Therefore, improvements in technological infrastructure and user assistance are required to ensure that the PUSAKA attendance system operates optimally and sustainably.